A Hybrid Model for Achieving Universal Safe Drinking Water in the Medium-Sized City of Bangangté (Cameroon) - Esther Laurentine Nya (MDPI AG, 2021)
Providing everyone with safe drinking water is a moral imperative. Yet, sub-Saharan Africa seems unable to achieve “safe drinking water for all” by 2030. This sad situation calls for a closer examination of the water supply options for both rural and urban populations. Commonly, two main aspects are considered: (1) behavioural responses to available or potential water supply options, and (2) socio-economic acceptability. These aspects determine the feasibility and the affordability of bringing safe drinking water as a basic good and human right to everyone. There is a broad consensus that achieving the UN Sustainable Development Goal 6.1 is mostly a financial issue, especially in low-income settings. This communication challenges this view as water is available everywhere and affordable treatment options are well-known. It considers the decentralized water supply model as a reference or standard approach in low-income settings rather than as an alternative. Here, the medium-sized city of Bangangté in the western region of Cameroon is used to demonstrate that universal safe drinking water will soon be possible. In fact, during the colonial period, the residences of the elite and the main institutions, including the administrative quarter, churches, and hospital, have been supplied with clean water from various local sources. All that is needed is to consider everyone as important or accept safe drinking water as human right. First, we present a historical background on water supply in the colonial period up to 1980. Second, the drinking water supply systems and water demand driven by population growth are discussed. Finally, a hybrid model for the achieving of universal access to clean drinking water, and preconditions for its successful implementation, are presented. Overall, this communication calls for a shift from safe drinking water supply approaches dominated by centralized systems, and presents a transferable hybrid model to achieve universal clean drinking water.